Safety and effectiveness of early compression of free flaps following lower limb reconstruction: A systematic review - Berner, JE; Will, P; Geoghegan, L; Troisi, L; Nanchahal, J; Jain, A (Elsevier, 2020)
Introduction Early postoperative compression of free flaps for lower limb reconstruction remains controversial. It may reduce venous congestion and promote the resolution of oedema. However, concerns remain regarding inadvertent pedicle compression, which may lead to flap failure. The aim of this systematic review was to determine the safety and effectiveness of this intervention.